IMPLEMENTASI KEGIATAN SENAM IRAMA DALAM MENGEMBANGKAN KEMAMPUAUN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK ISLAM MASJID AL FALAQ - Amara Julia Ratnaningsih; Wiwik Pudjaningsih; Syifa Fauziah; Nur Intan Rochmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop rhythmic gymnastics activities in the gross motor skills of children aged 5-6 years at the Al Falaq Mosque Islamic Kindergarten. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. During two learning sessions. In the first session, children were introduced to the rhythmic gymnastics activities of Anak Indonesia Hebat. The second session focused on introducing rhythmic gymnastics movements aimed at evaluating children's overall understanding. The results of this study indicate that rhythmic gymnastics creates a cheerful, interactive and fun atmosphere that encourages children to be more active and enthusiastic. Through rhythmic gymnastics videos, children are more motivated and enthusiastic in following each session. This contributes to increasing their self-confidence and social skills, as they learn to interact and cooperate with their peers. The role of teachers in improving gross motor skills of early childhood through rhythmic gymnastics activities at the Al Falaq Mosque Islamic Kindergarten as a facilitator who creates a fun learning environment, directs movements, and motivates children to actively participate in rhythmic gymnastics activities. Teachers are also responsible for designing activities that are appropriate to the child's development, ensuring that every movement made can improve muscle strength, balance, and coordination.